Cost-effectiveness analysis of left atrial appendage occlusion compared with pharmacological strategies for stroke prevention in atrial fibrillation. Issue 1 (December 2016) - Lee, Vivian; Tsai, Ronald; Chow, Ines; Yan, Bryan; Kaya, Mehmet; Park, Jai-Wun; Lam, Yat-Yin
Abstract Background Transcatheter left atrial appendage occlusion (LAAO) is a promising therapy for stroke prophylaxis in non-valvular atrial fibrillation (NVAF) but its cost-effectiveness remains understudied. This study evaluated the cost-effectiveness of LAAO for stroke prophylaxis in NVAF. Methods A Markov decision analytic model was used to compare the cost-effectiveness of LAAO with 7 pharmacological strategies: aspirin alone, clopidogrel plus aspirin, warfarin, dabigatran 110 mg, dabigatran 150 mg, apixaban, and rivaroxaban. Outcome measures included quality-adjusted life years (QALYs), lifetime costs and incremental cost-effectiveness ratios (ICERs). Base-case data were derived from ACTIVE, RE-LY, ARISTOTLE, ROCKET-AF, PROTECT-AF and PREVAIL trials. One-way sensitivity analysis varied by CHADS2 score, HAS-BLED score, time horizons, and LAAO costs; and probabilistic sensitivity analysis using 10, 000 Monte Carlo simulations was conducted to assess parameter uncertainty. Results LAAO was considered cost-effective compared with aspirin, clopidogrel plus aspirin, and warfarin, with ICER of US$5, 115, $2, 447, and $6, 298 per QALY gained, respectively. LAAO was dominant (i.e. less costly but more effective) compared to other strategies. Sensitivity analysis demonstrated favorable ICERs of LAAO against other strategies in varied CHADS2 score, HAS-BLED score, time horizons (5 to 15 years) and LAAO costs. LAAO was cost-effective in 86.24 % of 10, 000 simulations using a threshold of US$50, 000/QALY. Conclusions Transcatheter LAAO is cost-effective for prevention of stroke in NVAF compared with 7 pharmacological strategies. Condensed abstract The transcatheter left atrial appendage occlusion (LAAO) is considered cost-effective against the standard 7 oral pharmacological strategies including acetylsalicylic acid (ASA) alone, clopidogrel plus ASA, warfarin, dabigatran 110 mg, dabigatran 150 mg, apixaban, and rivaroxaban for stroke prophylaxis in non-valvular atrial fibrillation management.